Seasonal cravings: plant food preferences of syntopic small mammals. Issue 1 (2nd January 2018) - Gasperini, Stefania; Bonacchi, Andrea; Bartolommei, Paola; Manzo, Emiliano; Cozzolino, Roberto
Abstract : Having a thorough understanding of animal feeding behaviour is a basic aim in ecology. Food represents a crucial resource that can strongly rule animal populations, especially where food supplies are seasonal, such as in temperate areas. In Italy, sub-Mediterranean forests dominated by deciduous oaks are commonly inhabited by the yellow-necked mouse Apodemus flavicollis, the wood mouse A. sylvaticus and the bank vole Myodes glareolus . Despite the rich literature regarding their diet composition in northern Europe, to our knowledge no studies have been published on food preferences of these rodents in syntopy in sub-Mediterranean deciduous forests. Feeding preferences of 33 A. flavicollis, 10 A. sylvaticus and 18 M. glareolus on reproductive parts (flowers, unripe and ripe fruits) of 26 representative plant species in a deciduous oak forest of central Italy were investigated through seasonal cafeteria-style experiments. Our findings evidence that A. flavicollis exhibited distinct preferences in all seasons, highlighting a relevant affinity only for a strict array of plant species, and acting as seed specialist. Apodemus sylvaticus showed generalist food habits, eating all foods with similar consumption patterns, whereas M. glareolus occupied an intermediate position between the Apodemus spp. Indeed the bank vole did not show a clear preference for some foods over others in spring and summer, while in autumn the consumption significantly differed resulting in a strong preferences overlap with A. flavicollis . This result suggests potential competitive interactions between these rodents in our study area, especially regarding a crucial resource such as acorns. By using seasonal cafeteria-style experiments we were able to delineate the feeding behaviour and preferences of A. flavicollis, A. sylvaticus and M. glareolus towards several plant parts pertaining to a wide array of species. Our findings can help future studies regarding these rodents focusing on factors influencing their population dynamics, such as trophic resources and competition.